Simultaneous mechanical property and biodegradation improvement of wollastonite bioceramic through magnesium dilute doping. (February 2016) - Xie, Jiajun; Yang, Xianyan; Shao, Huifeng; Ye, Juan; He, Yong; Fu, Jianzhong; Gao, Changyou; Gou, Zhongru
Abstract: The large-area bone defects in head (including calvarial, orbital, and maxillofacial bone) and segmental bone are attracting increased attention in a wide range of clinical departments. A key requirement for the clinical success of the bioactive ceramics is the match of the mechanical behavior of the implants with the specific bone tissue to be filled. This raises the question as to what design strategy might be the best indicators for the balance between mechanical properties and biological performances. Here we go beyond the traditional approaches that use phase conversion or biphasic hybrid; instead, we achieved a simultaneous enhancement of several mechanical parameters and optimalization of biodegradability by using a dilute doping of Mg in a single-phase wollastonite bioceramic. We show that the wollastonite ceramic can be rationally tuned in phase (α or β), mechanical strength (in compression and bending mode), elastic modulus (18–23 GPa), and fracture toughness (>3.2 MPa m 1/2 ) through the usage of Mg dopant introduced at precisely defined dilute concentrations (Mg/Ca molar ratio: 1.2–2.1%). Meanwhile, the dilute Mg-doped wollastonite ceramics are shown to exhibit good bioactivity in vitro in SBF but biodegradation in Tris is inversely proportional to Mg content. Consequently, such new highly bioactive ceramics with appreciable strength and toughness are promising for making specific porous scaffolds for enhancing large segmental bone defect and thin-wall bone defect repair. Graphical abstract: